Zum Ausmaß bodenerosiver Abspülschäden in der Lößlandschaft des südöstlichen Harzvorlandes - Schröder, Hilmar; Löwa, Katrin (ERDKUNDE, 1991)
In the following paper the dimension of soil erosion on arable land caused by the process of downwash was investigated in the loess region near Querfurt (Sachsen-Anhalt) as apart of the south-eastern Harz-foreland. The points of departure were investigations of the potential erodibility and mapping - based on remote sensing - of the distribution of damage resulting from long lasting soil erosion. One may deduce from the position that one fifth of the arable land in the loess zone is heavily damaged by soil erosion. If we take in to consideration the fact that agriculture of the former GDR has to be structurally co-ordinated with the demands of the EC-market, a conversion has to be found for these fields, which will help to prevent future soil erosion. Ecological criteria, such as the construction of a system which links and takes account of various biotopes, ought to be accepted. The authors make proposals on protective measures as different steps. The recommendations are for non -agricultural use of the most heavily endangered areas, for pasture if endangered moderately, and for the building of structural walls in the case of terraces, and crop rotation on small fields on less endangered arable land.